The theoretical features of anthroponyms from the Arabic language on the Kazakh onomastic space (Eurasian Journal of Philology Science and Education, 2018)
The article is devoted to the study of personal names of the Arabic origin in the Kazakh onomasticspace from the point of view of religious knowledge. All events and phenomena occurring in the life ofsociety are reflected in the language. Especially spiritual and cultural innovations enrich the vocabularywith neologisms. Therefore, it is necessary to pay special attention to the functions performed by theproper name in language and speech. Along with the nominative, differentiating function, anthroponymsperform another, very important from the point of view of diachronic linguistics – cumulative or accumulative.A proper name is capable of reflecting, recording, storing information about a person’s reality,collective experience. People, when they give a name to a newborn, take into account those changesthat occur in the social life of the people. In connection with the spread of Islam, new names of Araborigin appeared in the Kazakh language. As a result of studying such anthroponyms from the point ofview of theology, a close connection of the names of one’s own with the spiritual world, faith and beliefsof people are established.